Legal Analysis of the Enforcement of Two Mortgage Rights on One Land Certificate as a Credit Collateral Object - Fitri Mustikaning Wibowo (UM Purwokerto Press, 2023)
The Civil Code provides two collateral institutions that can be used by the community, namely pawn and mortgage. Along with the development of law in Indonesia, there are two new collateral institutions, namely mortgages and fiduciaries. The definition of mortgage rights according to Article 1 point 1 of Law Number 4 of 1996 concerning Mortgage Rights on Land and Objects Associated with Land is a security institution attached to the object in the form of land rights. In practice, one land object can be charged by more than one mortgage right. This research aims to find out and analyze the laws and regulations in Indonesia that regulate the encumbrance of more than one mortgage right on a land object and understand the technical auction of a land object encumbered by more than one mortgage right. This research is written using the normative juridical method through the Law and case approach with binding primary legal materials and secondary legal materials as references. The result of this research is legal certainty against debt repayment with land object collateral that has been encumbered by more than one mortgage.